Kinetic Study of Methyl Orange Wastewater Degradation of Catalytic Wet Air Oxidation by Fe-Co Activated Carbon - Gu, Jinchuan; Wei, Chunmei; Tan, Baojun; Mei, Ziliang (Asian Journal of Chemistry, 2013)
Catalyst was prepared by the impregnation method using Fe-Co as active component, activated carbon as carrier. The sorption kinetics of methyl orange wastewater on Fe-Co activated carbon was investigated. The results indicate the catalytic wet air oxidation could be described using the first order kinetics, which was fitted well with the experimental data. It had a significant impact on the degradation rate that the dye of active component and the initial ClO2 concentration. Moreover, the lower activation energy of shows the reaction can be initiated easily.